Pharmaceutical compounds in urban drinking waters of Ecuador - Jara-Negrete, Eliza; Cipriani-Avila, Isabel; Molinero, Jon; Pinos-Vélez, Verónica; Acosta-López, Sofía; Cabrera, Marcela; Medina-Villamizar, Evencio Joel; Leiva-Andrade, David; Pozo, Andrea; Martínez, Omar; Mogollón, Noroska G.S. (Frontiers in Environmental Science, 2023)
Introduction: Emerging contaminants (ECs) are substances with widely diverse chemical structures that may pose a risk to the environment and human beings. The limited scope of water treatment facilities, particularly in low and middle-income countries, allows ECs to be continuously introduced to the environment and become part of the cycle again for potabilization. In this work, we study for the first time the presence of these compounds in the drinking water of five Ecuadorian cities. Methods: The compounds of interest were mainly pharmaceutical substances commonly present in prescription and over-the-counter medicines, along with caffeine, a known coadjuvant in some of these preparations. Samples were collected from Quito, Guayaquil, Cuenca, Ibarra, and Esmeraldas, considering each city’s distribution systems, and, after solid-phase extraction, analyzed by LC-MS/MS ESI+. Results and discussion: Results showed a high occurrence of caffeine, the only analyte present in all cities, with concentrations ranging from <6.35 to 201 ngL-1 and an occurrence from 11% in Quito to 77% in Cuenca. The highest median was found in Cuenca, followed by Esmeraldas. Our observations regarding concentrations are comparable to other studies around the globe. Although in other cities, some pharmaceuticals appeared at levels below our detection limits. These findings highlight the ubiquitous nature of emerging contaminants while pointing out the need for regulatory frameworks that facilitate the implementation of treatment technologies at the source and wastewater level. These actions will safeguard public and environmental health in the long term.